Sources of Cardiovascular Health Information and Channels of Health Communication among Urban Population in Nigeria - Ejiofor Augustine Ezika; Beth Cross; Moira Lewitt (International Journal of Public Health Science (IJPHS), 2018)
This study employed mixed methods to investigate the preferred sources of health information and later explored the views of community healthcare workers on the enablers, barriers and ways of overcoming barriers to health communication. The study found that majority of the participants preferred their source of CV (cardiovascular) health information from the healthcare workers including the medical doctors, nurses, and pharmacists. On the other hand, the least preferred source of health information was from friends, family members, and community leaders. Some of the identified enablers to community health communication include awareness programme via Non-Governmental Organisations (NGOs), community-based organisations such as faith-based organisations and healthcare facilities. Others are traditional media and social media. The identified barriers to community-based health communication include lack of knowledge and poverty, language barriers, and other miscellaneous issues including misuse of internet, lack of basic amenities and religious beliefs. The community-based healthcare providers articulated ways to overcome the identified barriers, including enlightenment programmes, using the language of the target audience, funding health awareness programmes, and monitoring of health education interventions. This study concludes that dissemination of health information using numerous channels is essential in ensuring population-wide primary prevention of diseases.